Ordered Statistics And Their Importance In Finding The Distribution Of Variation Series Terms - Gulnoz Sayfulloyeva; Shokirova Durdona; Ibragimova Dildora; Bozorboyeva Dildora (Genius Journals, 2024)
Ordinal statistics play an important role in mathematical statistics. In many cases, ordinal statistics are used as estimates in problems of estimating unknown parameters. In order to check the properties of these estimates and to assess their error, it is necessary to know the distributions of ordinal statistics. Therefore, the study of ordinal statistics and their distributions is of great importance. This qualification thesis is devoted to these issues.
Keywords: Random Variables; Unordered Variables; Ordered Variables